Auditory Brainstem Changes in Timing may Underlie Hyperacusis in a Salicylate-induced Acute Rat Model. (1st February 2020) - Duron, Julie; Monconduit, Lénaic; Avan, Paul
Highlights: After salicylate (150 mg/kg), rats experience a mean 4-fold increase in acoustic startle strength reflecting hyperacusis. The mean middle-ear muscle reflex threshold increased from 55 to 80 dB SPL after salicylate. The mean latencies of auditory brainstem-evoked responses decreased by 0.25 millisecond at low frequencies only. Brainstem timing changes induce intense hyperacusis in a cross-frequency-coincidence spatiotemporal model of loudness. Abstract: Hyperacusis, an exaggerated, sometimes painful perception of loudness even for soft sounds, is a poorly understood distressing condition. While the involvement of modified gain of central auditory neurons and the influence of nonauditory brain regions are well-documented, the issue of where in the auditory system these abnormalities arise remains open, particularly when hyperacusis comes without sensorineural hearing loss. Here we used acute intraperitoneal administration of sodium salicylate (150 mg/kg) in rats, enough to produce > 10-dB decrease in acoustic startle threshold with mild hearing loss at low frequencies (<10 kHz). Anesthesia, necessary for middle-ear-reflex (MEMR) threshold measurements, abolished the olivocochlear efferent reflex but not the MEMR acting on frequencies < 10 kHz, and its mean threshold increased from 55 dB SPL in controls to 80 dB SPL in salicylate-treated animals 60–90 minutes after injection, with an about 3-dB increase in acoustic energy reaching the cochlea. The mean latencies of auditory brainstem-evoked responses (ABR) conspicuously decreased after salicylate, by 0.25 millisecond at 6 kHz at every level, a frequency-dependent effect absent above 12 kHz. A generic model of loudness based upon cross-frequency coincidence detection predicts that with such timing changes, a transient sound may seem as loud at <40 dB SPL as it does in controls at >60 dB SPL. Candidate circuits able to act at the same time on the startle reflex, the MEMR and ABRs may be serotoninergic, as salicylate is known to increase brain serotonin and 5-HT neurons participate in MEMR and ABR circuits.